Innovation and market concentration with asymmetric firms - Marc Escrihuela-Villar (Goethe University Frankfurt, Center for Financial Studies (CFS), 2004)
This paper considers a theoretical model of n asymmetric firms that reduce their initial unit costs by spending on R&D activities. In accordance with Schumpeterian hypotheses we obtain that more efficient (bigger) firms spend more in R&D and this leads to a more concentrated market structure. We also find a positive relationship between innovation and market concentration. This calls for a corrective tax on R&D activities to curtail strategic incentives to over-invest in R&D trying to achieve a higher market share.
urn:nbn:de:hebis:30-10555
Keywords: L11; L52; O31; 330; R&D; Asymmetries; Market Concentration; Optimal Industrial Policies; Industrieökonomik; Innovation; Wirtschaftskonzentration; Industriepolitik; Theorie